Research on phase equilibrium effect and curve vacuum membrane-based dehumidification device. (August 2020) - Chun, Liang; Gong, Guangcai; Peng, Pei; Li, Wenqiang; Fang, Xi
Highlights: The importance of phase equilibrium effect in vacuum membrane-based dehumidification process is analyzed. A novel inversion method is proposed to predict the apparent water vapor permeability A novel model is established to investigate the novel curve vacuum membrane-based dehumidification device. Abstract: In this work, the importance of phase equilibrium effect in vacuum membrane-based dehumidification process is analyzed. A novel inversion method is proposed to predict the apparent water vapor permeability under the effect of phase equilibrium. In addition, a novel method derived from kinetic theory and Reynolds transport theory is established to investigate the novel curve vacuum membrane-based dehumidification device. In terms of physical mechanism, this novel method is reasonable and appropriate. Results indicate that the phase equilibrium has a positive effect on vacuum membrane-based dehumidification, and it can increase dehumidification efficiency by 4.65% 8.14%. The apparent water vapor permeability calculated by the inversion method is about 60% higher than the water vapor permeability measured by cup method. When the curvature radius is reduced from 30mm to 15mm, the dehumidification efficiency of convex membrane and concave membrane increase by 1.96% and 1.74% respectively. Compared with concave membrane, convex membrane can increase the dehumidification efficiency by 0.185% 0.414%. Thus, the recommended curved membrane is convex membrane, because it could increase the flow boundary-layer thickness at some corners. This work can provide a simulation method and engineering design reference for the field of vacuum membrane-based dehumidification technology.